Global Sensitivity of Simulated Water Balance Indicators Under Future Climate Change in the Colorado Basin. Issue 1 (12th January 2018) - Bennett, Katrina E.; Urrego Blanco, Jorge R.; Jonko, Alexandra; Bohn, Theodore J.; Atchley, Adam L.; Urban, Nathan M.; Middleton, Richard S.
Abstract: The Colorado River Basin is a fundamentally important river for society, ecology, and energy in the United States. Streamflow estimates are often provided using modeling tools which rely on uncertain parameters; sensitivity analysis can help determine which parameters impact model results. Despite the fact that simulated flows respond to changing climate and vegetation in the basin, parameter sensitivity of the simulations under climate change has rarely been considered. In this study, we conduct a global sensitivity analysis to relate changes in runoff, evapotranspiration, snow water equivalent, and soil moisture to model parameters in the Variable Infiltration Capacity (VIC) hydrologic model. We combine global sensitivity analysis with a space‐filling Latin Hypercube Sampling of the model parameter space and statistical emulation of the VIC model to examine sensitivities to uncertainties in 46 model parameters following a variance‐based approach. We find that snow‐dominated regions are much more sensitive to uncertainties in VIC parameters. Although baseflow and runoff changes respond to parameters used in previous sensitivity studies, we discover new key parameter sensitivities. For instance, changes in runoff and evapotranspiration are sensitive to albedo, while changes in snow water equivalent are sensitive to canopy fraction and Leaf Area Index (LAI) in the VIC model. It is critical for improved modeling to narrow uncertainty in these parameters through improved observations and field studies. This is important because LAI and albedo are anticipated to change under future climate and narrowing uncertainty is paramount to advance our application of models such as VIC for water resource management. Plain Language Summary: The Colorado River Basin is a fundamentally important river for society, ecology, and energy in the United States. In this study, we conduct a sensitivity analysis to relate changes in streamflow and other water balance changes such as evapotranspiration, snow, and soil moisture to model parameters in a hydrologic model. We find that snow‐dominated regions are much more sensitive to uncertainties in our model parameters. We also discover new key parameter sensitivities, for example, changes in runoff and evapotranspiration are sensitive to the reflectivity of the Earth's surface, while snow water equivalent is sensitive to parameters related to vegetation canopy size. It is critical for improved hydrological modeling to narrow uncertainty in these parameters through improved observations and field studies. This is particularly important because we know that these parameters are anticipated to change in the future. It is imperative that we improve our hydrological models to make correct decisions for basin‐scale water resource management and planning, particularly in the water‐stressed Southwestern United States. Key Points: Global sensitivity analysis and statistical emulation is used to examine uncertainties in VIC model parameters for the Colorado River For snow‐dominated basins, changes in runoff, evapotranspiration, and soil moisture are sensitive to baseflow with key interdependencies Changes in snow water equivalent are influenced by LAI and albedo for which field observations and remote sensing require improvement